PENGARUH PEMBELAJARAN JARAK JAUH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI DI KABUPATEN BANDUNG - Yusup syarifudin bakri; Ikaputera Waspada; Rasto Rasto (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2021)
This research is motivated by the low learning outcomes of students in economic subjects in SMA Negeri in Bandung Regency. The purpose of this study was to find out and analyze how the description of distance learning and student learning outcomes, the effect of distance learning on learning outcomes. The method used in this study was an explanatory survey with data collection techniques through questionnaires and observation. The population of this research is the students of class XI IPS SMA Negeri in Bandung Regency as many as 2,495 students, while the sample is 364 students. The data that has been collected is then analyzed using descriptive statistical analysis and path analysis. The results showed that: (i) distance learning was in the medium category, learning motivation, and student learning outcomes were in the medium category. (ii) distance learning has an effect on learning outcomes.Keywords: Distance Learning, Learning Outcomes In Economics Learning